The regulation of takeovers in New Zealand and returns to shareholders : a thesis presented in partial fulfilment of the requirements for a Master of Business Studies at Massey University - Kittle, Andrew Gordon (Massey University, 2001)
Between 1 January 1996 and 30 June 2001 takeovers in New Zealand were governed by a set of regulations that formed part of New Zealand Stock Exchange ("NZSE") listing rules. The NZSE rules were relatively light in their approach to governing takeovers and received much criticism throughout their tenure. Prior to 1 January 1996 takeovers had been regulated by the Companies Amendment Act 1963. We examine the returns to targets and bidders between 1 January 1990 and 30 June 2000 to determine how effective the rules were in promoting shareholder wealth. The change in regulations between 1995 and 1996 also presents an opportunity to examine the impact on returns from moving from a lightly regulated regime to one which is more regulated with a greater amount of required disclosure. We find that returns to both targets and bidders were lower under the NZSE regime than under the Companies Amendment Act 1963. This result is attributed to several specific aspects of the Companies Amendment Act 1963 such as the ability of the target to recover defense costs from bidder and a set period for which the offer must remain open.
Keywords: Valuation; New Zealand; Law and legislation; Consolidation and merger of corporations; Corporations